Bionomics of Culex quinquefasciatus within urban areas of Rio de Janeiro, Southeastern Brazil - David, Mariana Rocha; Ribeiro, Gabriel Sylvestre; Freitas, Rafael Maciel de (Revista de Saúde Pública, 2012)
OBJECTIVE: To evaluate density, parity rates, daily survival and longevity of natural populations of Culex quinquefasciatus in three neighborhoods with distinct socio-economic and infrastructure profiles. METHODS: Mosquito collections of the Culex quinquefasciatus species were performed weekly during two four month periods, from August to November 2008 (spring) and March to June 2009 (fall), in a favela (slum), a suburban area and a middle class area of Rio de Janeiro, Southeastern Brazil. Collections were performed with backpack aspirators, in 20 randomly selected houses in each area per week, during 15-20 minutes per house. Ovaries were removed from captured females and classified as initial, intermediary or final stage. Furthermore, females were dissected for determination of parity based on the condition of the tracheal system. Mosquito survival rate and longevity were estimated on a per month basis for each neighborhood. RESULTS: We collected a total of 2,062 Culex quinquefasciatus, but monthly vector density was not correlated with temperature and rainfall. We dissected the ovaries of 625 Culex quinquefasciatus, and overall, there was a higher proportion of nulliparous females during the dryer months, while gravid females were more frequent in rainy months. In the middle class neighborhood, the parity rate reached up to 93.75% with survivorship of 0.979. Lower parity and survival rates were obtained in the suburban area (as low as 36.4% parity and 0.711 daily survival). Up to 84.7% of Culex quinquefasciatus females could survive the eight day period needed to complete West Nile Virus incubation. CONCLUSIONS: The survival rate of Culex quinquefasciatus varied significantly between the neighborhoods. This suggests that vectorial capacity and disease transmission risk may vary greatly between different urban areas, which is potentially useful information for vector control programs.